Characteristics of a magnetically levitated flexible rotor when in contact with one or more auxiliary bearings - Keogh P.S. (2014)
The case for installing auxiliary bearings in parallel with magnetic bearings is often made with regard to touchdown, when a complete system failure occurs. The work reported in this paper focuses on the case when rotor/auxiliary bearing contact occurs, but the magnetic bearings retain their functionality. One may envisage future transportation applications in which this situation would occur, for example, during high acceleration levels induced by turbulence. An understanding of the rotor dynamic response during contact conditions could enable auxiliary bearing life expectancy to be extended using appropriate control action from the still functional magnetic bearings. To achieve this, a system model is required for control strategy design purposes. This paper considers the development of a non-linear system model for predicting the contact dynamics in a flexible rotor/magnetic/auxiliary bearing system. Previous experimental work produced similar contact dynamic response characteristics; whether due to unbalance or circular forcing through a magnetic bearing. Initial model-based predictions of these tests did not provide sufficiently accurate reproduction of the measured orbits, particularly in the presence of auxiliary bearing misalignment and multi-plane rotor contact. Parameter variations are thus undertaken to investigate the reasons for these differences. Contrary to expectations, uncertainty in the magnetic bearing characteristics during contact conditions appears to offer an explanation. Copyright © 2005 by ASME.